Who Buffers Income Losses after Job Displacement? The Role of Alternative Income Sources, the Family, and the State - Daniel Fackler; Eva Weigt (LABOUR, 2019)
Using survey data from the German Socio-Economic Panel (SOEP), this paper analyses the extent to which alternative income sources, reactions within the household context, and redistribution by the state attenuate earnings losses after job displacement. Applying propensity score matching and fixed effects estimations, we find that income from self-employment reduces the earnings gap only slightly and severance payments buffer losses in the short run. On the household level, we find little evidence for an added worker effect whereas redistribution by the state within the tax and transfer system mitigates income losses substantially.
Keywords: 380